Exploring the Contributing Factors of Polycystic Ovary Syndrome (PCOS) - Hussain, Meqdad; Shaikh, Farah; Jamil, Laiba; Shaheen, Aania; Afaq, M.Hashir; Hasni, Abrar Ahmed; Waseem, Mohammad Wasiq; Khalid, Maryam (Indus Journal of Bioscience Research, 2025)
Background: PCOS, a complex endocrine disorder, primarily affects those of reproductive age, emerging in late teens or early twenties. It involves hormonal imbalances, notably heightened androgen levels and insulin resistance. Clinical manifestations include irregular menstrual cycles, hirsutism, and acne. Sedentary lifestyle and poor dietary choices worsen symptoms, leading to weight gain and increased insulin resistance. Obesity often coexists, intensifying metabolic issues. A family history raises the risk. Complications encompass infertility, type 2 diabetes, cardiovascular disease, and mood disorders. A balanced diet, regular exercise, and holistic PCOS management positively impact symptoms and associated complications. Methodology: This study employed a cross-sectional design to collect data from 50 diagnosed PCOS patients using a pre-structured questionnaire. Participants were selected based on specific inclusion criteria from, Holy Family and DHQ Hospital Rawalpindi. Results: The study revealed a diverse participant distribution, with 42% aged 19-24 and 40% aged 25-34. Most were married (64%), and hormone test results varied, notably with abnormal levels in testosterone (34%) and irregular menstrual cycles affecting 92%. Insulin levels were elevated in 14%, while 74% engaged in regular exercise. Dietary habits ranged from healthy (26%) to unhealthy (12%). Stress concerned 92%, and 70% used treatments for PCOS, addressing health issues like fertility problems (62%) and skin/hair issues (90%). Family history of PCOS or hormonal disorders was reported by 46%. Conclusion: Our study contributes nuanced insights into the complex landscape of PCOS, emphasizing the importance of tailored interventions and holistic care. our findings provide a deeper understanding of the interconnections between demographic, clinical, and lifestyle factors, paving the way for further research and targeted interventions in PCOS management.